2017
DOI: 10.4018/ijeoe.2017040104
|View full text |Cite
|
Sign up to set email alerts
|

Neural Fuzzy Control of Ball and Beam System

Abstract: This paper presents an offline control of ball and beam system using fuzzy logic. The objective is to control ball position and beam orientation using fuzzy controllers. A Matlab/Simulink model of the proposed system has been designed using Newton's equations of motion. The fuzzy controllers were built using seven gbell membership functions. The performance of proposed controllers was compared in terms of settling time, steady state error and overshoot. The simulation results are shown with the help of graphs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Typically, a backpropagation-type learning algorithm is applied to identify fuzzy rules and learn the membership functions of the fuzzy reasoning. Several studies 4,3033,118120 have shown that neural fuzzy systems can be successfully used to control underactuated systems.…”
Section: Control Methods Based On Fuzzy Systems For Underactuated Sysmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, a backpropagation-type learning algorithm is applied to identify fuzzy rules and learn the membership functions of the fuzzy reasoning. Several studies 4,3033,118120 have shown that neural fuzzy systems can be successfully used to control underactuated systems.…”
Section: Control Methods Based On Fuzzy Systems For Underactuated Sysmentioning
confidence: 99%
“…The neuro-fuzzy system’s parameter was updated using a critic module. In Kharola and Patil, 120 the authors applied a neural fuzzy system to control a BAB system.…”
Section: Control Methods Based On Fuzzy Systems For Underactuated Sysmentioning
confidence: 99%
“…In [29], the equations of the ball and beam system in [28] were scaled according to time and torque. In the past few years, more and more new control methods have been used to control a ball and beam system, such as fuzzy logic, neural networks, robust control and backstepping [30][31][32][33]. A comparative study was conducted for models of ball and beam systems in [34].…”
Section: Introductionmentioning
confidence: 99%
“…This approach however necessitates the utilization of sophisticated tools and hardware, potentially limiting its applicability to smaller or less complex control systems. Previous studies have also explored the use of nonlinear controllers such as neural networks [22]- [25], fuzzy logic [26]- [29], backstepping [30], deep reinforcement learning [31], and passivity-based control [32], as alternative strategies for stabilizing the BnB system.…”
Section: Introductionmentioning
confidence: 99%